Management of Educational Facilities and Infrastructure to Improve the Quality of Education - Nuril Chusna, Via; Faridah, Ida; Kumala, Shofa Aulia (Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the management of facilities and infrastructure administration as a strategy in improving the quality of education at Pejengkolan State Elementary School. The research focus includes the planning, utilization, maintenance, and development of educational facilities and infrastructure. This research uses a qualitative approach with data collection techniques in the form of interviews, observations, and documentation. The research informants consisted of school principals, administrative staff, teachers, and education staff. The results of the study show that the management of facilities and infrastructure administration that is carried out systematically through structured planning, transparent budgeting, routine maintenance, and the involvement of school stakeholders makes a positive contribution to the creation of a conducive learning environment and the improvement of learning quality. Strategic management in the management of facilities and infrastructure not only supports the operational efficiency of schools, but also plays an important role in improving the quality of education. This study concludes that strengthening the administration and management of facilities and infrastructure is an important factor in realizing a sustainable improvement of the quality of education in elementary schools.